1999
DOI: 10.1111/1468-0262.00071
|View full text |Cite
|
Sign up to set email alerts
|

Error Bands for Impulse Responses

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
475
1
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 753 publications
(491 citation statements)
references
References 25 publications
12
475
1
3
Order By: Relevance
“…As recommended by Sims and Zha (1999), we report the impulse response functions (solid line) together with 68% 12 probability bands (dashed lines). 16 The median value is chosen as the central measure of impulse responses.…”
Section: Stock Marketmentioning
confidence: 99%
See 1 more Smart Citation
“…As recommended by Sims and Zha (1999), we report the impulse response functions (solid line) together with 68% 12 probability bands (dashed lines). 16 The median value is chosen as the central measure of impulse responses.…”
Section: Stock Marketmentioning
confidence: 99%
“…[FIGURE 1 HERE] 16 According to Sims and Zha (1999), the traditional symmetric confidence intervals, reported as one or two standard errors around the point estimate of an impulse response function, may be misleading. Such error bands confound information regarding the location of the coefficient values with the information about the overall model fit.…”
Section: Stock Marketmentioning
confidence: 99%
“…Once more, the prior mean is assumed to be 10 When the prior in equation (2) has a symmetric structure (i.e., it differs by only a scale factor across the equations) the posterior conditional on A 0 is multivariate normal. See Kadiyala and Karlsson (1997), Sims and Zha (1999), and . 11 This does not mean we are assuming the data follow a random walk.…”
Section: Bayesian Structural Vector Autoregessionsmentioning
confidence: 99%
“…The degree of uncertainty about the dynamic (impulse) responses of medium and large scale systems inherits the serial correlation that is part of the endogenous systems of equations. Hence conventional methods for constructing error bands around them are inadequate (Sims and Zha 1999). 28 How then do we select from among competing theoretical and statistical specifications?…”
Section: Model Uncertaintymentioning
confidence: 99%
“…For example, it can lead to sufficiently distorted CIs with such severe spurious asymmetry that the bootstrap CIs do not even include the estimated IRF. Sims andZha (1999, p. 1125, fn 13) note that some SVAR studies have found it necessary to "use a modification of [the bootstrap…”
Section: Introductionmentioning
confidence: 99%